Diverse Profiles of AI-1 Type Quorum Sensing Molecules in Cultivable Bacteria from the Mangrove (Kandelia obovata) Rhizosphere Environment - Ma, Zhi P.; Lao, Yong M.; Jin, Hui; Lin, Guang H.; Cai, Zhong H.; Zhou, Jin (Frontiers in Microbiology, 2016)
Mangrove rhizosphere environment harbors diverse populations of microbes, and some evidence showed that rhizobacteria behavior was regulated by quorum sensing (QS). Investigating the diverse profiles of QS molecules in mangrove ecosystems may shed light on the bacterial roles and lead to a better understanding of the symbiotic interactions between plants and microbes. The aims of the current study focus on identifying AI-1 type QS signals, i.e. acyl homoserine lactones (AHLs), in Kandelia obovata rhizosphere environment. Approximately 1200 rhizobacteria were screened and 184 strains (15.3%) tested were positive. Subsequent 16s rRNA gene sequencing and dereplication analyses identified 24 species from the positive isolates, which were affiliated to three different phyla, including Proteobacteria, Firmicutes and Actinobacteria. Thin-layer chromatography (TLC) separation of extracts revealed diverse AHL profiles and detected at least one active compound in the supernatant of these 24 cultivable AHL-producers. The active extracts from these bacterial isolates were further evaluated by ultra performance liquid chromatography-mass spectrometry (UPLC-MS), and the carbon side chain length ranged from C4 to C14. This is the first report on the diversity of AI-1 type auto-inducers in the mangrove plant K. obovata, and it is imperative to expand our knowledge of plant-bacteria interactions with respect to the maintenance of wetland ecosystem health.